STUDI IDENTIFIKASI KANDUNGAN FORMALIN PADA IKAN TERI NASI ASIN DI PASAR TRADISIONAL DAN PASAR MODERN KOTA SEMARANG - Purba, Widya Kristiani Dory; Darundiati, Yusniar Hanani; Dewanti, Niki Astorina Yunita (Jurnal Kesehatan Masyarakat (Undip), 2015)
Salted anchovy  containing formaldehyde can be found in traditional markets and modern markets. Formaldehyde is a chemical which harmful to human health.In the long term formaldehyde can cause cancer and death to humans.The purpose of this study is to identify the content of formaldehyde in salted anchovy which sold in traditional markets and modern in Semarang city.This research is a descriptive study with qualitative examination of the formaldehyde content in  salted anchovy. The method used  is survey method. The population in this study is the salted anchovy seller in traditional markets and modern markets in Semarang city numbering 41 people. Samples using total sampling.The instrument used was a questionnaire used during open interviews. The result of this study is as much as 31 samples (88.57%) of the 35 samples examined were found to contain formaldehyde, one sample of which is a sample derived from modern market. All the traders (100%) disagree with the use of formalin in food . A total of 88.75 % (31 sellers) get salted anchovy in the city of Semarang. Sellers are replacing salted anchovy once a week as much as 31,43% (11 sellers). Sellers who lack the knowledge that is as much as 91,43 % formalin (32 sellers) do not know formaldehyde thus the necessity of socialization for both sellers and consumers regarding the symptoms of formaldehyde poisoning and danger to human health It is important for public health office to provide counseling for seller and consumers regarding symptoms of formaldehyde poisoning and danger to human health.